Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3168/jds.2011-4169
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Associations between variables of routine herd data and dairy cattle welfare indicators

Abstract: As farm animal welfare is high on the political and societal agendas of many countries, considerable pressure exists to establish audit programs in which farm animal welfare is routinely monitored. On-farm assessment of animal welfare, however, is time-consuming and costly. A promising strategy to monitor animal welfare more efficiently is to first estimate the level of animal welfare on a farm based on routine herd data that are available in national databases. It is not currently known which variables of rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 154 publications
(251 reference statements)
1
74
0
3
Order By: Relevance
“…de Vries et al, 2011). For goats, recorded production variables were found to be unrelated to other animal-based welfare indicators (Muri et al, 2013), but we found significant differences in SCCs and milk yield between HG and non-HG herds in this study.…”
Section: Registered Datamentioning
confidence: 36%
“…de Vries et al, 2011). For goats, recorded production variables were found to be unrelated to other animal-based welfare indicators (Muri et al, 2013), but we found significant differences in SCCs and milk yield between HG and non-HG herds in this study.…”
Section: Registered Datamentioning
confidence: 36%
“…Less severe, but much more frequent and persistent, is SARA in which feed intake and performance may be suppressed. SARA is also associated with other health problems, such as inflammation (liver abscesses or laminitis) associated with pain (Plaizier et al, 2009) or bloat and displaced abomasum (Nocek, 1997;Enemark, 2008;De Vries et al, 2011). In beef cattle, the health problems associated with acidosis reduce productivity (e.g.…”
Section: Contribution Of Livestock To Global Greenhouse Gas Emissionsmentioning
confidence: 99%
“…However, as already described by Rauw et al (1998) and Lawrence et al (2004), selective breeding for higher productivity can harm animal health and welfare unless balanced by selection pressure placed on functional traits. Genetic selection for high production efficiency can impair normal biological functioning (Oltenacu, 2009;De Vries et al, 2011;Fraser et al, 2013) and lead to numerous unexpected consequences (Table 1). A high genetic potential for mobilizing body energy reserves for production can have deleterious effects on health and fertility (Bell et al, 2011), as shown by the association between high milk production and an increased incidence of fertility problems and metabolic disorders such as ketosis in dairy cattle (Walsh et al, 2011).…”
Section: Contribution Of Livestock To Global Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Fertility KPIs as indicators of animal welfare Fertility KPIs may also be indicators of animal welfare (de Vries et al, 2011). Specifically the 120-day in-calf rate and the percentage of heifers not mated by 17 months of age, have been suggested as indicators of poor animal welfare in a herd (Nyman et al, 2011).…”
Section: Discrepancies In Terminology and Definitions Of Kpismentioning
confidence: 99%